(untitled) (Journal of Atomic and Molecular Sciences, 2016)
Two-dimensional (2D) molybdenum disulfide (MoS_2) promised a wide range of potential applications. Here, we report the transport investigations on the MoS_2 from Armchair (AC) and Zigzag (ZZ) directions with different kinds of leads. The conductance of 2H phase MoS_2 depended on the transport directions and lead types (2H phase or 1T phase). System with 1T phase MoS_2 as lead can impressively improve the transport properties compared with the 2H phase lead. Moreover, for the system with metal lead, enhanced conductance can be observed, which contrast to the experiment measurements. Further investigation indicated that the conductance sensitively relies on the distance between metal lead and 2D material. The present theoretical results suggested the lead material and interface details are both important for MoS_2 transport exploration, which can provide vital insights into the other 2D hybrid materials.